Clozapine-related obsessive–compulsive symptoms and their impact on wellbeing: a naturalistic longitudinal study - Parkin, K; Chen, S; Biria, M; Plaistow, J; Beckwith, H; Jarratt-Barnham, I; Segarra, N; Worbe, Y; Fineberg, NA; Cardinal, RN; Robbins, TW; Fernandez-Egea, E (Cambridge University Press, 2022)
Background Obsessive–compulsive symptoms (OCS) are commonly associated with clozapine treatment but are frequently overlooked by clinicians despite their potential impact on patients' quality of life. In this study, we explored whether OCS severity impacted subjective wellbeing and general functioning, independently of depressive and psychotic symptoms.